You have 5 seconds: designing glanceable feedback for physical activity trackers - Gouveia, Rúben; Pereira, Fábio; Caraban, Ana; Munson, Sean A.; Karapanos, Evangelos (My University, 2015)
People engage with activity trackers in short sessions: over 70% are defined by glances - brief, 5-second sessions where individuals check ongoing activity levels with no further interaction. We explore how to best leverage such short sessions to maximize positive impact on behavior. To do so, we explore the design of Glanceable Behavioral Feedback Interfaces, focusing on three directions for design: increasing the frequency of glances, increasing the impact of glances on physical activity, and promoting moments of exploration and learning with activity trackers.
Keywords: Behavioral feedback interfaces; Engagement; Glanceable displays; Physical activity tracking